The Impact of Domestic Investment, Economic Growth, Open Unemployment and Zis Funds on Poverty in Indonesia, 2008 – 2022 - Wardani, Dhias Pramudita Kusuma; Rizkia, Reza Fitriana; Rizqi, Salsa Bela Putri; Andni, Riyan; Afandi, Johan; Yingxiang, Schunk; Xin, Derr (Journal International Dakwah and Communication, 2023)
Poverty is a problem that is still being faced in every region in Indonesia. So several things must be considered in handling it. In Islam the solution to reducing poverty can be done by using ZIS especially since Indonesia is the largest Muslim country in the world with a total of 231.06 million people. In Indonesia, the management of ZIS funds is always increasing. During the Covid-19 pandemic, the ZIS funds collected experienced an increase which was expected to reduce the poverty rate that occurred in Indonesia. The purpose of this study was to examine several variables that affect poverty levels including Domestic Investment, Economic Growth, Open Unemployment and ZIS Funds (Zakat, Infaq, Sadaqah). This study used a quantitative approach and secondary data taken from BPS and National Development Planning Agency for 2008 – 2022. The data was processed using the E-views 9 application with the classical assumption test, multiple regression test, and hypothesis testing. The results showed that the investment and economic growth variables had no significant effect with a probability value of 0.1362 and 0.6077, the open unemployment variable had a significant effect with a probability value of 0.01 and had a positive direction with a coefficient of 5.989262, while the ZIS variable had no significant effect with a probability value of 0.40 and has a positive direction with a coefficient of 0.209688. The implication of this research is to increase the awareness of the Indonesian people regarding zakat in order to reduce the poverty rate in Indonesia.